2010
DOI: 10.1016/j.applthermaleng.2009.11.019
|View full text |Cite
|
Sign up to set email alerts
|

Numerical modelling of geothermal vertical heat exchangers for the short time analysis using the state model size reduction technique

Abstract: This is a PDF file of an unedited manuscript that has been accepted for publication. As a service to our customers we are providing this early version of the manuscript. The manuscript will undergo copyediting, typesetting, and review of the resulting proof before it is published in its final form. Please note that during the production process errors may be discovered which could affect the content, and all legal disclaimers that apply to the journal pertain. ACCEPTED MANUSCRIPT AbstractAccording to the intr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
27
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 57 publications
(28 citation statements)
references
References 8 publications
1
27
0
Order By: Relevance
“…Esen et al [9] developed a two-dimensional Finite Element Model (FEM) to simulate the temperature distribution of the soil surrounding the GHEs of GCHPs in both cooling and heating operation modes. Kim et al [10] introduced a state model size reduction technique to reduce the required time for numerical simulation of GHEs. In another study, a new cumulative constant heat flux (CCHF) model for simulating the behavior of the GHE, was developed by Li [11] and Bouhacina et al [12].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Esen et al [9] developed a two-dimensional Finite Element Model (FEM) to simulate the temperature distribution of the soil surrounding the GHEs of GCHPs in both cooling and heating operation modes. Kim et al [10] introduced a state model size reduction technique to reduce the required time for numerical simulation of GHEs. In another study, a new cumulative constant heat flux (CCHF) model for simulating the behavior of the GHE, was developed by Li [11] and Bouhacina et al [12].…”
Section: Introductionmentioning
confidence: 99%
“…5.The measurement of the soil temperature adopts the thermocouple temperature sensors and the computer records data through the data acquisition instrument. In order to monitor the variation of soil temperature near the GHE at different depth, a total number of 36 thermocouple temperature sensors were set in 3 boreholes measuring the annual soil temperature at 5 m,10 m,15 m, 20 m, 30 m, 40 m, 50 m, 60 m, 70 m, 80 m, 90 m and 100 m underground for each borehole. For data reliability, the average value of the 3 measured temperatures at the same depth is calculated as the final result.…”
mentioning
confidence: 99%
“…Instead of using the Robin boundary condition, Christodoulides et al [22] used a source/sink term in the governing equation to account for the heat transfer between the fluid and the tube, assuming the heat transfer within the tube body was instantaneous because the thickness of the tube was extremely thin. An interesting modeling approach was proposed by Kim et al [23], who applied a Model Order Reduction (MOR) technique to develop a computationally efficient model for the numerical analysis of a vertical borehole heat exchanger. Kim et al [23] combined a vertical slice model with a Finite Element discretization of horizontal cross sections and validated it against analytical solutions.…”
Section: Introductionmentioning
confidence: 99%
“…An interesting modeling approach was proposed by Kim et al [23], who applied a Model Order Reduction (MOR) technique to develop a computationally efficient model for the numerical analysis of a vertical borehole heat exchanger. Kim et al [23] combined a vertical slice model with a Finite Element discretization of horizontal cross sections and validated it against analytical solutions. The authors reported a computational time reduction of 95% compared to a fully 3D model.…”
Section: Introductionmentioning
confidence: 99%
“…Finally, the finite elements model (FEM) is one of the most detailed models currently available [18,19,20,21,22,23]. This model uses a very fine discretization of the BHE, which produces the most accurate results, although having a very high computational cost.…”
Section: Introductionmentioning
confidence: 99%